Toll Gate Vehicle Monitoring System – A Preview - Newlin Rajkumar, M; Ranjani, M; Venkatesa Kumar, V (International Journal of Computer Sciences and Engineering, 2025)
Advance in technology, there is a different aspect of designing and allotting number plates to the vehicle of their country. For the several respective regular administrative tasks, the license number plate is used by various government offices for purposes of tracking of number plates, for the analysis of theft case, for the collection and management of parking vehicles. The unique number is given for each motorized vehicle in India. Vehicles play a vital role because of population growth. For various security purposes vehicle number has to be stored. The number plate is recognized to extract number of the plate faster. The character recognition technique is used to recognize numbers and character from number plate. Then recognized the number and character is stored in a cloud storage system as and used for further needs.